Ritual Nanggai Summang Pada Perkawinan Umat Hindu Kaharingan di Desa Tanjung Jawa Kabupaten Barito Selatan - Derson Derson (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2023)
Preserving a tradition is an obligation of all parties, especially Hinduism Kaharingan people who are in the area of Tanjung Jawa Village, South Barito Regency. Religion and ritual are always in synergy as the birth of a religion is based on a ritual or tradition and cultural traditions are based on religion. Along with development in nowadays whereby the existence of the Nanggai Summang marriage ritual has almost disappeared and rarely conduct anymore, it is caused by the influence of moderation culture in rapid way with the result that the local culture has become a tradition that contains a lot of meaning, religious, socio-cultural and traditions are put aside. In fact, the marriage ritual of Nanggai Summang needs to be maintained to be a guide for the young generation, in order to prevent the marriage ritual. The Nanggai Summang marriage ritual is a marriage which is conducted as a result of marriage which still having close family relations with uncle, aunt, first or second cousin and nephew. As the consequences of the marriage, it is an obligation to conduct Nanggai Summang ritual. The Nanggai Summang ritual has two meanings, which are: (1) to purify the couple who violate the provisions of the applicable customs (2) to purify the village or area which affect by the wrong marriage and (3) as a purification of the surrounding nature which causes lahing liha (heat). This marriage pretty much used to exist because the people had faith in it and believed in its impact and if the Nanggai Summang ritual was not conducted, then it would have big impact, such as lack of harmony in building a household, giving birth to children with disabilities physically or mentally, and the people around them would suffer various problems, such as disease outbreaks, many agricultural products are damaged and fruit trees will not produce perfect fruit.